Level of knowledge about oral cancer in dental students of the Universidad Científica del Sur - Segura Gaspar, Paula (2021)
ABSTRACT Objective: The objective of this study was to determine the level of knowledge about oral cancer of third, fourth and fifth year students of the professional career of dentistry at the Southern Scientific University in 2020. Materials and methods: A questionnaire was carried out on knowledge of oral cancer to 166 students who were in the third, fourth and fifth year of dentistry. This questionnaire consisted of 24 multiple-choice questions about epidemiology, etiopathogenesis, diagnosis, treatment and complications. Results: A significant association was found between the level of knowledge about the etiopathogenesis of oral cancer and the year of study. Conclusion: Third-year students had the highest percentage in relation to the level of knowledge about etiopathogenesis.